Kemampuan dan Kemauan Pasien Umum Rawat Inap Dalam Membayar Pelayanan Kesehatan Rawat Inap di Rumah Sakit Umum Kaliwates Kabupaten Jember - Anafia, Yanuar; Witcahyo, Eri (UI Scholars Hub, 2019)
testRational rates were determined by calculating unit costs into account characteristics of product as information related ability and willingness to pay. Ability and willingness were calculated for quality control and cost at the hospital. Community satisfaction index in Kaliwates General hospital released number of customer satisfaction that hasn’t met the standard was rate of inpatient services. Results of preliminary study on general inpatients were 70% having an estimated rate of less than rate set by the hospital, 20% said rates were less affordable and 10% couldn’t estimate rates, then this study was calculate ability and willingness to pay for inpatient health services at the Kaliwates General Hospital. This study was an analytical study conducted on 91 general inpatients at Kaliwates General Hospital with total population sampling technique. The real value of ATP obtained has an average of IDR 438,101 with largest ability category was high ability at intervals ≥ IDR 409,375 and estimation of willingness to pay,WTP1 has an average of 256,923 and WTP2 has an average of 300,714,- The advice is calculation of unit cost with due regard ability and willingness to pay, development of inpatient rooms according to community needs,improvement of medical personnel,and development of information delivery innovations.